Islam, Postmodernism and Other Futures: A Ziauddin Sardar Reader by Sohail Inayatullah and Gail Boxwell, eds. (London and Sterling, VA: Pluto Press, 2003. 374 pages.) (American Journal of Islam and Society, 2004)
Followers of the Islamization of Knowledge project probably know thework of Ziauddin Sardar best for its trenchant critique of that project. Yetthe prolific British-Pakistani intellectual has written thoughtfully on topicsranging from the social consequences of science and technology and thefuture development of Muslim societies to cultural studies and the impactof postmodernism on religious belief. Since Sardar’s work is scatteredacross books, academic journals, and science and news magazines, the Reader is a most welcome compendium that showcases the breadth of hisengagements.The book contains 20 selections, which are divided almost equally intothree sections; the editors' introduction, which I discuss below; and a workingbibliography of Sardar's writings and index, both of which are very usefuladditions ...